AKTIVITAS ANTIBAKTERI DAN ANALISIS EKSTRAK AKAR PARANG ROMANG (Boehmeria virgata (Forst) Guill) METODE KLT-BIOAUTOGRAFI - Evi Mustiqawati (Jurnal Sains dan Teknologi Laboratorium Medik, 2021)
The plant has active chemical compounds which is able to be functioned as antibacterial, one of them is called parang romang (Boehmeria virgata (Forst) Guill). Bacteria is a living thing which can cause many diseases. Multidrug resistance is one needs to be paid attention to. Therefore, science and health development is a new challenge for the progress of bringing a new solution to antibiotics. Several multinational studies were conducted to determine the prevalence of herbal use in infections caused by microorganisms. The use of plant substances such as alkaloids, organosulfur compounds, phenolic acids, flavonoids, carotenoids, coumarins, terpenoids, tannins, has been the interest of recently research as the part of a development in science and health. The purpose of this study was to determine the antibacterial activity of the root extract of parang romang (Boehmeria virgata (Forst) Guill) towards the Streptococcus mutans and Pseudomonas aeruginosabacteria as well as to identify the chemical components in the root extract of parang romang as antibacterial. The results of the study were found at the Rf value in the TLC-Bioautography test; it obtained 0.09; 0.27; 0.36; and the active chemical components in the extract of the root of parang romang (Boehmeria virgata (Forst) Guill) gave positive results on the appearance of the spots in terms of the terpenoid group., alkaloids, phenols and flavonoids. The conclusion of this study is the root extract of parang romang (Boehmeria virgata (Forst) Guill) at the concentration of 1mg/mL can inhibit the Streptococcus mutans and Pseudomonas aeruginosa